REVITALISASI KONSEP RUMAH TANGGA SAKINAH DI ERA MODERN: PENDEKATAN TEMATIK HADIS TERHADAP TANTANGAN DAN SOLUSI KEHIDUPAN MUSLIM - Jasmin, Suriah Pebriyani; Aisyah, Siti; Abdul Rahman Sakka (IAIN BONE, 2025)
This article examines the revitalization of the concept of a sakinah family in the modern era through a thematic analysis of hadiths concerning marital relations, family responsibilities, consultation, and compassion among family members. Amid the influence of globalization, value secularization, and digital media that shape communication patterns and moral dynamics within Muslim families, the reinterpretation of prophetic values becomes essential to maintain relevance and adaptability. Using a qualitative, library-based method, the study identifies key themes such as spiritual communication, gender justice, compassionate education, and ethical use of technology. The findings emphasize that revitalizing the sakinah concept must be grounded in the maqāṣid al-sharī‘ah, including the protection of religion, life, intellect, lineage, and property. The implementation of hadith values highlights the importance of compassionate communication, just relationships, and ethical child education, as well as the wise use of digital technology to support prophetic principles. This study offers an integrative paradigm that harmonizes prophetic values with modern challenges as a practical guide for Muslim families.